PENGARUH PENGGUNAAN GAME ONLINE MOBILE LEGEND TERHADAP PERILAKU KOMUNIKASI SISWA SMA NEGERI 1 KENDARI - Prasetya, Yoga Yudha; La Tarifu, La Tarifu; La Iba, La Iba (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
ABSTRACTThis study aims to determine and analyze the Effect of Online Game Mobile Legend on Communication Behavior of Students SMA Negeri 1 Kendari. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. Data were analyzed using simple regression analysis. The population of this research is the XI grade students of SMA Negeri 1 Kendari who have used legend mobile online games with a total of 318 students in which only 14% or 45 students were sampled for this study. The results of this study indicate that the online game mobile legend has a positive effect on communication behavior.Â Key Words : Online Game; Mobile Legend;Communication Behavior